Basal Stem Rot of Oil Palm : Incidence, Etiology and Control - Hashim, Khairudin (1990)
Basal stem rot (BSR) caused by Ganoderma spp. is a disease of economic importance in oil palm in Malaysia. Although much is known on the occurrence of this devastating disease, fundamental studies on it and its pathogen are rather limited. At present, there appears to be ambiguity in the identity of the causal organisms: there is difficulty in getting oil palms to be artificially infected and that control measures advocated are largely inadequate to contain the disease. Present studies are thus focused on answering these issues. An assessment of the BSR situation on selected estates was also carried out to assist in the understanding of the disease. The assessment carried out showed that serious incidence of the disease was "confined to coastal and riverine estates. However, the disease can now be seen to occur in a few in land estates albeit sporadically and at very low incidence. It was demonstrated that previous crops did not necessarily dict ate significant incidence of BSR. The underplanting technique and certain soil types can predispose plantings to much higher BSR incidence.